Życie religijne mieszkańców Wielkopolski w II Rzeczypospolitej na przykładzie miasta Czarnkowa - Pałka, Damian (Ecclesia. Studia z Dziejów Wielkopolski, 2010)
In 1919 - after more than a hundred years of German dominance - Czarnków returned into Polish hands. During the interwar period three nationalities inhabited Czarnków: Poles, Germans and Jews. The Jewish population was a separate group not only ethnic, and also religious terms. The German element, until then predominating in the town, was reduced to a minority. The article consists of two parts: the first part presents problems related to the social structure and religious activity of Catholics, the second part deals with the fates of the local Protestant population.